2011
DOI: 10.1080/10158782.2011.11441457
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii Infection in HIV-positive and HIV-negative subjects in Gauteng, South Africa

Abstract: Toxoplasmosis is an infection of warm-blooded vertebrates caused by one of the most common parasites of humans, Toxoplasma gondii. T. gondii is an obligate intracellular protozoan parasite with a worldwide distribution and a varying prevalence between different continents and countries, and even within the same country. There is little known about T. gondii prevalence in Africa. In South Africa, there is limited information about the disease and detailed recent demographic data of groups at risk are missing. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 14 publications
6
34
6
Order By: Relevance
“…Prevalence of toxoplasmosis: Data for 88 countries (Flegr et al 2014) were supplemented with six other countries: Botswana (Joubert and Evans, 1997), Kenya (Kamau et al 2012), Lebanon (Usta et al 2006), Namibia (Joubert and Evans, 1997), Uganda (Lindstrom et al 2006), and Zambia (Kistiah et al 2011). The final list contains data on prevalence of toxoplasmosis (seroprevalence) in women of childbearing age published mostly between 1995 and 2008 for 94 countries, 30 European; see Table 1.…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence of toxoplasmosis: Data for 88 countries (Flegr et al 2014) were supplemented with six other countries: Botswana (Joubert and Evans, 1997), Kenya (Kamau et al 2012), Lebanon (Usta et al 2006), Namibia (Joubert and Evans, 1997), Uganda (Lindstrom et al 2006), and Zambia (Kistiah et al 2011). The final list contains data on prevalence of toxoplasmosis (seroprevalence) in women of childbearing age published mostly between 1995 and 2008 for 94 countries, 30 European; see Table 1.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Year in which the given study has been carried out is shown in the fourth column, the fifth column states the number of women in the sample and the last one gives sex ratio at birth (SRB). Data for 88 countries published in Flegr et al (2014) have been supplemented with six other countries: Botswana (Joubert and Evans, 1997), Kenya (Kamau et al 2012), Lebanon (Usta et al 2006), Namibia (Joubert and Evans, 1997), Uganda (Lindstrom et al 2006), and Zambia (Kistiah et al 2011 Contraceptive use, which indicates the proportion of women of reproductive age who are using (or whose partner is using) a contraceptive method for the period of 2005-2009, was obtained from the World Bank (2011). Total fertility estimates for the year of 2008 were taken from the World Bank (2011).…”
Section: Independent Variablesmentioning
confidence: 99%
“…The first reported study was from South Africa, by Mason, Jacobs and Fripp 2 in 1974, whereby a seroprevalence of 20% was found in a cohort comprising black, white, Indian and coloured immunocompetent individuals. Since then, other studies, the most recent being Kistiah et al, 18 have reported a 6.4% seroprevalence in a generalised cohort, but it was biased towards pregnant women. Swai and Schoonman 16 reported seroprevalence of 45.7% in a Tanzanian cohort predominantly comprising immunocompetent individuals who were exposed to livestock via their occupation (abattoir workers, livestock keepers and animal health workers).…”
Section: Toxoplasmosis In Immunocompetent Individualsmentioning
confidence: 98%
“…The disease may be a recrudescence of a latent infection or a newly acquired toxoplasmic infection. It may result from rupture of the cyst and conversion of the bradyzoites into the tachyzoites within the tissue of the retina or elsewhere in the body [1]. If not treated early or promptly, Toxoplasmic encephalitis is a fatal disorder.…”
Section: Introductionmentioning
confidence: 99%
“…This parasite is mainly caused by the obligate inOpen Access tracellular protozoan T. gondii. It considered one of the most successful parasites on earth, since it has the ability to maintain a benign coexistence with its host [1]. Moreover, toxoplasmosis is the most common among patients with AIDS.…”
Section: Introductionmentioning
confidence: 99%